2011
DOI: 10.5101/nbe.v3i4.p203-210
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic PCR Chips

Abstract: The microfluidic polymerase chain reaction (PCR) chips have undergone extensive development and nowadays have become an important domain of miniaturization technology application. Here, we review the advances of microfluidic PCR chips over the past years, from the first single chamber stationary PCR chip to the new SlipChip PCR. First, the three distinct types of microfluidic PCR chips are discussed, including chamber stationary PCR chips, flow-through PCR chips and convection PCR chips. Then we focus on dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Microfluidics as a contemporary technology offers a multitude of application possibilities by manipulating fluids in microchannels and is becoming increasingly important not only in point-of-care testing, analysis, biotechnology, and chemistry but above all for the formulation of NP-based pharmaceuticals and personalized medicine [ 18 , 19 ]. Nowadays, reams of microfluidic chips are available with all kinds of geometries that control the fluids and the mixing of fluids either actively or in a passive manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics as a contemporary technology offers a multitude of application possibilities by manipulating fluids in microchannels and is becoming increasingly important not only in point-of-care testing, analysis, biotechnology, and chemistry but above all for the formulation of NP-based pharmaceuticals and personalized medicine [ 18 , 19 ]. Nowadays, reams of microfluidic chips are available with all kinds of geometries that control the fluids and the mixing of fluids either actively or in a passive manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are significantly changing the way of processing chemical and biological analysis [5,6], cell and gene analysis [7,8], drug discovery and clinical diagnostics [9,10], material synthesis [11,12] and environmental monitoring [13,14]. Among them, the applications in biology and medicine research and related areas are almost the most extensive and profound.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemiluminescence-based detection is also known to have certain shortcomings, such as, poor selectivity and low emission intensity generated by the chemical reactions catalyzed by enzymes in small volumes, which is due to the low efficiency in transforming chemical energy into light [6]. Several strategies were developed to enhance the chemiluminescence emission of chemical reactions catalyzed by enzymes (i.e., enzymatic reactions) [7]. For example, Diaz et al have demonstrated the use of fluorescein has an enhancer on the chemiluminescence of luminol with horseradish peroxidase (HRP) [8].…”
Section: Introductionmentioning
confidence: 99%